Reseña de Laura GALIÁN (2020). Colonialism, Transnationalism, and Anarchism in the South of the Mediterranean. Springer Nature. - Escalante Moreno, Helios (Revista de Estudios Internacionales Mediterráneos, 2021)
Reseña de Laura GALIÁN (2020). Colonialism, Transnationalism, and Anarchism in the South of the Mediterranean. Springer Nature.